Measuring Neural Arousal for Advertisements and Its Relationship With Advertising Success - Eijlers, Esther; Boksem, Maarten A. S.; Smidts, Ale (Frontiers in Neuroscience, 2020)
Abundant research has established the important role of ad-evoked feelings on consumers’ reaction to advertising. However, measurement of feelings through explicit self-report is not without its limitations. The current study adds to previous work by showing a sophisticated way of first estimating how arousal is represented in the brain via an independent task (using EEG), and thereafter using this representation to measure arousal in response to advertisements. We then estimate the relationship between the identified process (arousal) and external measures of ad effectiveness (as measured by notability and attitude toward the ad). The results show that the neural measure of arousal is positively associated with notability of ads in the population at large, but may be negatively associated with attitude toward these ads. The implications for the application of EEG in ad testing and for understanding the relationship between arousal and effective advertising are discussed.